Properties of Arsenic–Doped ZnTe Thin Films as a Back Contact for CdTe Solar Cells - Ochai Oklobia (Materials, 2019)
As-doped polycrystalline ZnTe layers grown by metalorganic chemical vapor deposition (MOCVD) have been investigated as a back contact for CdTe solar cells. While undoped ZnTe films were essentially insulating, the doped layers showed significant rise in conductivity with increasing As concentration. High p-type carrier densities up 4.5 × 1018 cm−3 was measured by the Hall-effect in heavily doped ZnTe:As films, displaying electrical properties comparable to epitaxial ZnTe single crystalline thin films in the literature. Device incorporation with as-deposited ZnTe:As yielded lower photovoltaic (PV) performance compared to reference devices, due to losses in the open-circuit potential (VOC) and fill factor (FF) related to reducing p-type doping density (NA) in the absorber layer. Some minor recovery observed in absorber doping following a Cl-free post–ZnTe:As deposition anneal in hydrogen at 420 °C contributed to a slight improvement in VOC and NA, highlighting the significance of back contact activation. A mild CdCl2 activation process on the ZnTe:As back contact layer via a sacrificial CdS cap layer has been assessed to suppress Zn losses, which occur in the case of standard CdCl2 anneal treatments (CHT) via formation of volatile ZnCl2. The CdS sacrificial cap was effective in minimising the Zn loss. Compared to untreated and non-capped, mild CHT processed ZnTe:As back contacted devices, mild CHT with a CdS barrier showed the highest recovery in absorber doping and an ~10 mV gain in VOC, with the best cell efficiency approaching the baseline devices.